Hematological Profiles of Pregnant Women with Nutritional Anemia: Insights into Diagnostic Challenges and Clinical Implications - Ahmad, Ayesha; Khan, Tamkin; Fatima, Bushra; Nishad, Suman (International Journal of Human and Health Sciences (IJHHS), 2025)
Background: Anemia in pregnancy is a significant global health concern, often associated with adverse maternal and fetal outcomes. Objective: This study aims to examine the hematological profiles of pregnant women with nutritional anemia, focusing on diagnostic challenges and clinical implications. Methods: This retrospective study was conducted at Jawaharlal Nehru Medical College and Hospital (JNMCH), Uttar Pradesh, India, to analyze hematological parameters in pregnant women unresponsive to routine iron and folic acid therapy. Case records of anemic patients who had received at least four weeks of oral iron and folic acid supplementation without significant improvement in hemoglobin levels were included. Patients with known hematological disorders, chronic diseases, or incomplete records were excluded. Hematological parameters analyzed included hemoglobin levels, total leukocyte count (TLC), platelet count, and general blood picture findings. Patients were categorized into microcytic hypochromic anemia and dimorphic anemia groups. Results: Microcytic hypochromic anemia was the most prevalent type, though a significant proportion of cases exhibited dimorphic anemia. Dimorphic anemia was associated with higher TLC values, indicating a potential inflammatory or immune response, and lower platelet counts, suggesting a possible risk of thrombocytopenia. The findings highlight the heterogeneity of dimorphic anemia and its implications for treatment strategies. Conclusion: The study underscores the diagnostic complexities of anemia in pregnancy, particularly in differentiating between iron deficiency anemia and mixed nutritional deficiencies. Routine hematological screening, supplemented by biochemical assays for vitamin B12 and folate levels, is crucial for accurate classification and management. Improved screening protocols and targeted supplementation strategies are essential in resourcelimited settings to optimize maternal and fetal health outcomes. International Journal of Human and Health Sciences Vol. 09 No. 02 Apr’25 Page: 107-112